Sustaining the Unsustainable? Political Accountability and Development in sub-Saharan Africa’s Resource Economies - Ndlovu, Xichavo Alecia (University of the Witwatersrand, Johannesburg, 2023)
Sub-Saharan Africa’s development challenge is to ‘sustain the unsustainable’–using non-renewable resources to initiate long-term development processes that outlive the short-term proceeds of resource extraction. Literature has highlighted how differences in political institutions help determine whether natural resources help or hinder development. However, there is disagreement on which political institutions account for the variations in development outcomes. This study clarifies whether political regimes, electoral competitiveness, and party institutionalisation matter for inclusive and sustainable development using a sample of all sub-Saharan African countries for which data is available from 1990 to 2018. Specifically, do democracies perform better or worse on average than non-democracies? Do electorally competitive democracies perform better or worse than dominant-party (but still multiparty) democracies? Do more institutionalised party systems perform better or worse than less institutionalised party systems? In general, how, if at all, do different political accountability mechanisms affect inclusive and sustainable development? The study uses ‘nested’ analysis, which combines cross-national statistical analysis and case studies of four resource-rich democracies in Africa: Ghana, Zambia, Namibia, and Mozambique. The cross-national analysis shows that party institutionalisation is the only political predictor for social inclusiveness, and all political variables do not improve or worsen economic sustainability. On the other hand, resource rents are negatively associated with social inclusiveness but do not predict economic sustainability. Meanwhile, the non-rent sectors contribute positively to both dimensions of development, highlighting the potential significance of income levels in explaining the cross-national development patterns in Africa. Evidence in the case studies shows that electorally competitive democracies outperform dominant party democracies on social inclusiveness. The risk of being removed from office incentivises incumbents to provide public goods and increase social welfare. However, the impact of political accountability mechanisms on economic sustainability is ambiguous and may depend on sectoral institutions, policies and actors. The study contributes to (and bridges) two groups of literature, one investigating the economic consequences of politics and institutions and another accounting for the resource curse. It also considers both the inclusivity and sustainability aspects of development and highlights contextual factors from case studies, often overlooked in cross-national analyses.
Thesis submitted to fulfil the requirements for the Doctor of Philosophy degree in International Relations at the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, Johannesburg, South Africa, 2023.
Keywords: Political accountability; Sustainable and inclusive development; Natural-resource governance; Democracy; Political parties; Sub-Saharan Africa; UCTD; SDG-16: Peace, justice and strong institutions